Generalizing the behavior of flash-boiling, plume interaction and spray collapse for multi-hole, direct injection. (15th July 2017) - Lacey, J.; Poursadegh, F.; Brear, M.J.; Gordon, R.; Petersen, P.; Lakey, C.; Butcher, B.; Ryan, S.
Abstract: This paper presents an experimental and modeling study of direct fuel injection in a constant volume chamber (CVC). Iso-octane and propane are used as surrogates for gasoline and liquefied petroleum gas (LPG) respectively, and are injected over a wide range of conditions that are relevant to modern, spark ignition engines. Optical imaging of the liquid and vapor phases are first used to examine these sprays' overall behavior. These experimental results and thermodynamic arguments are then used to demonstrate the limitations of some existing methods for identifying the onset of spray plume interaction and spray collapse in multi-hole injectors. Further modeling is then undertaken, leading to new criteria for both spray collapse and plume interaction due to flash-boiling. These criteria employ simple physical arguments, geometrical parameters and the fuel's thermodynamic property data, and appear to be applicable to any fuel injector.